Can a web‐based food record accurately assess energy intake in overweight and obese women? A pilot study. (17th March 2013) - Hutchesson, M. J.; Truby, H.; Callister, R.; Morgan, P. J.; Davies, P. S. W.; Collins, C. E.
Abstract: Background: Innovative dietary intake measurement tools, such as web‐based food records, are becoming increasingly available for self‐monitoring. However, the accuracy of this method has not been well studied. This pilot study aimed to evaluate the accuracy of energy intake (EI) estimated by a web‐based food record, by comparison with total energy expenditure (TEE) measured by doubly‐labelled water (DLW) in overweight and obese women. Methods: Total energy expenditure (TEE) was assessed in weight stable (±1 kg) women ( n  = 9), with a mean (SD) age of 34.5 (11.3) years and body mass index of 29.2 (1.4) kg m –2 over 10 days using the DLW technique. All food and beverages were self‐reported for 9‐days using a web‐based food record and mean daily EI calculated. Food record accuracy was assessed by calculating the absolute (EI − TEE) and percentage (EI/TEE × 100) differences between EI and TEE. Women were identified as under‐reporters of EI based on the 95% confidence limits of the expected EI : TEE of 1. Results: The mean (SD) self‐reported EI was 8351 (1225) kJ day −1 [1996 (293) kcal day −1 ] and TEE was 10 648 (1774) kJ day −1 [2545 (424) kcal day −1 ]. The mean (SD) absolute difference in self‐reported EI and TEE was −2301 (1535) kJ day −1 [−550 (367) kcal day −1 ], representing a mean reporting accuracy of 79.6% (14.1%), with four participants under‐reporting EI. Conclusions: This pilot study highlights the opportunity for the use of the Internet as a novel medium for recording and assessing dietary intake. Although further research is needed in more diverse population groups, the accuracy of web‐based food records for assessing EI appears to be consistent with other published dietary intake methods.